Fungi on indoor walls and their management by fungicides (Bangladesh Journal of Botany, 2015)
Fungal colonies were found growing as patches round the year on the distempered indoor damp walls of ground floor of the Department of Botany, University of Dhaka. Fungi were isolated and identified as Cladosporium oxysporum Berk & Curt., Curvularia lunata (Wakker) Boedijn and species of Fusarium and Penicillium. Fungicides namely, bendazin 50% WP, calixin, champion 75 WP, companion, mancozeb and provex were sprayed on the indoor damp walls to control the fungal growth. All the fungicides controlled the growth of all fungi except C. oxysporum at 500 ppm concentration which was controlled by 1000 ppm. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21681 Bangladesh J. Bot. 43(2): 239-242, 2014 (September)